(untitled) (Research, Society and Development, 2021)
In order to evaluate different levels of probiotic in diets for Nile tilapia post-larvae, 1,680 Nile tilapia post-larvae (0.05 ± 0.01g) were distributed in 24 110 L aquariums, in a completely randomized design with six treatments and four replications, considering as an experimental unit an aquarium with 70 fry. During the experiment, water quality parameters were monitored daily using a portable multiparameter probe and the water temperature (26.9 ± 0.5 ° C), dissolved oxygen (4.0 ± 0.7mg / L), electrical conductivity were evaluated. (170.1 ± 46.6 μS / cm) and pH (7.2 ± 0.5). A basal diet (control - 0.00) was formulated and levels of inclusion of probiotic of the genus Bacillus 4.0x 1012 CFU (0.02; 0.04; 0.06; 0.08; 0.10 g / 100g) were performed) of feed. At the end, the parameters of zootechnical performance and centesimal composition of the carcass were evaluated, where no differences were observed (P <0.05) on the evaluated parameters. Bowel histology was performed, and the height and width of the villi and thickness of the tunic were measured, where influence (P <0.05) on the width of the villi and tunic thickness was observed, which showed better responses in the levels of inclusions. higher probiotics (0.08 and 0.10 g). Although, there is no positive influence of the levels of inclusion of probiotic of the genus Bacillus in the diet do not influence the zootechnical performance of Nile tilapia, it is recommended to include 0.08g / kg of probiotic of the genus Bacillus for presenting improvement in intestinal health of Nile tilapia post-larvae.